PTH-075 You'Ve Gut Mail: A Gastroenterology Email Helpline Is Efficient and Cost-Effective in Resolving Patient Queries and Reducing Non-Elective Inpatient Bed Days. (4th June 2013) - Ooi, J L S; Vinayaga-Pavan, M; Koh, D C K; Morgan, V; Wong, V S
Abstract : Introduction: Electronic patient-provider communication may be a convenient, cost-effective complement to standard healthcare services 1 . We piloted a dedicated gastroenterology (GI) email helpline to increase accessibility for patients and medical colleagues seeking specialist advice. Methods: Retrospective study of activity records of our GI specialist nurse-led email helpline across 40 months (Jan 2008-Jul 2010; Feb-Dec 2012). Data for 2012 was analysed to demonstrate efficiency. From our highest frequency user group – inflammatory bowel disease (IBD) patients – we identified a cohort of 21 users that had contact with our department 6 months before their index email, comparing hospital utilisation rates then and in the 6 months afterward (post-intervention). Analysis was by Mann-Whitney and χ² tests. Cost savings were estimated based on Department of Health Reference Costs 2011/12. Results: The helpline received 264 emails from 153 users over 40 months: 73% from patients, 20% from GPs, 7% from others. Of 126 patients, 57% were female, 43% male. Mean age was 42.4 years (range 18–82 years). 2012 data analysis: Of 72 email queries, 72% were successfully resolved electronically. Mean turnaround time was 2.2 working days (range 0–9). 69% (50 emails) concerned general advice, medications or results, queries that are conventionally handled in outpatients (OP; £141/appointment) or in telephone clinic (TC; £55/appointment). Only 8.5% of email queries subsequently required TC encounters; another 10% proceeded to OP. By approximating 1 hour's work per week for a GI specialist nurse at £22/hour2, we estimate the email service cost £1144 in 2012, plus £1317 for ensuing TCs and OPs, a total of £2461. This compares favourably to £2750 to answer the 50 queries by TC alone, or £7050 by OP alone. Highest uptake was among the IBD subgroup: 49 users generated 129 emails over 40 months. In the 6 months pre- & post-index email, our identified cohort (n = 21) had similar rates of clinic attendance (41 vs 53 appts, p > 0.05), DNAs (3 vs 3) and A&E attendance (4 vs 0 visits, p > 0.05). Reduction in non-elective inpatient bed days was significant (34 vs 4 days, p < 0.0001; £271/day), representing savings of £8130 over 6 months. Conclusion: Our GI email helpline has proven to be popular and economical. Most queries were resolved electronically, significantly reducing unscheduled inpatient bed days. We are planning a user satisfaction survey to measure quality. A prospective study is warranted as our service expands. Disclosure of Interest: None Declared. References: Impact of electronic messaging on the patient-physician interaction. Wallweiner M et al. J Telemed Telecare. 2009; 15(5):243–250 Royal College of Nursing (2012) Inflammatory bowel disease nursing, London: RCN. Publication code 004 197